Longitudinal Investigation of Psychotherapy Outcomes (LIPO): Description of the Study Protocol - Gonçalves, Leonardo; Barbisan, Guillherme Kirsten; Rebouças, Cinthia Danielle Araújo Vasconcelos; da Rocha, Neusa Sica (Frontiers in Psychiatry, 2019)
Background: Despite extensive research in the field of psychotherapies, few studies have compared the primary psychotherapies of naturalistic design, which represents real-life situations. Objective: This study aims to follow-up outpatients from a psychotherapy clinic at a university hospital. Methods: One hundred and twenty-six patients receiving one of three modalities of individual psychotherapy will be included: psychodynamic psychotherapy (PDT), interpersonal psychotherapy (IPT) and cognitive-behavioral psychotherapy (CBT). The follow-up period will be baseline, 6 months and 1 year after entering the study. We will include 42 controls. Our sample size calculation considered a significance level of 5%; a power of 80% to detect a difference of 0.22 with a standard deviation of 0.43. We assumed losses of 20–30% of patients. Results: Due to the difficulty defining outcomes in psychotherapy and the lack of consensus in this regard, we divided our primary outcomes into three domains of variables: clinical (general psychiatric symptoms), biological (serum BDNF levels) and psychosocial (resilience, quality of life, coping strategies, social support, quality of life-adjusted years of life). Confounding/mediator variables included clinical (personality traits; type of psychotherapy, number of sessions, concomitant use of pharmacological treatment, history of previous psychotherapeutic treatment, medical and psychiatric comorbidities, psychiatric diagnosis); psychosocial (psychosocial stressors, therapeutic alliance and defense mechanism style) and other (religiosity) factors. Discussion: We will compare the outcomes of the primary psychotherapies to understand their mediating and confounding mechanisms to provide a basis for their better indication and understanding of their processes in patients with severe mental illness. This work will contribute to the formation of evidence-based public health policies in the field of psychological interventions.